City Deals in the polycentric state: The spaces and politics of Metrophilia in the UK. (October 2019) - Waite, David; Morgan, Kevin
This paper draws attention to the burgeoning phenomenon of Metrophilia, the fashionable yet uncritical embrace of city-centric narratives of development in place-based policymaking. Within this narrative, City Deals have emerged as mechanisms that pit places in competition with each other through the promotion of local economic growth compacts. Despite being launched with great fanfare as localised victories, City Deals raise important questions regarding the shape of the UK state system and the objectives of spatial policy. Addressing these concerns, and focusing on the tripartite political arrangement in the UK's devolved administrations nations, we argue that political tensions between nationalism and city-regionalism may be exacerbated through deal-making approaches.